Methods for providing heat to electric operated LNG plant - Tangås, Cecilie Magrethe (Institutt for energi- og prosessteknikk, 2010)
Hammerfest LNG plant, located at Melkøya outside Hammerfest, is supplied with heat and power from an on-site combined heat and power (CHP-) plant. This natural gas fired CHP emits more than one million tons of CO2 per year, which makes it one of Norway s largest point emissions. Melkøya is therefore of large interest when it comes to reducing the national CO2 emissions. Previous work has identified import of renewable electricity from the national grid to power the LNG plant as the most promising solution to reduction in the CO2 emissions from Melkøya.This report assesses different heat generation alternatives when co-generation is no longer applicable, in order to find the optimal solution for Melkøya, with respect to CO2 emission and operability. The most promising alternatives were subject to simulation, where CO2 emission, fuel/ power demand etc. were identified.Heat pumps are found to be the thermodynamically most favourable alternative. It is not able to cover the entire heat demand at Melkøya, but used in combination with other methods of heat generation, the result is significantly reduced fuel and power consumption, as well as CO2 emissions.Further investigation of use of heat pumps as heat providers at Melkøya is therefore recommended.